Business Model Development With The Approach Of Business Model Canvas At Hs Rent Cars (International Journal of Environmental Sciences, 2025)
The car rental industry is a sector that continues to grow along with the increasing need for flexible and practical transportation mobility in society. Nationally, the development of car rental businesses in Indonesia shows a positive trend. However, car rental business actors face obstacles in dealing with the dynamics of the growth of the car rental market. HS Rent Cars faces various problems that affect its competitiveness in the competitive car rental market. The main obstacles include the limited fleet of vehicles, which prevents it from meeting the increase in customer demand. The lack of diverse vehicle variations limits the ability to serve a wider customer segment. The high operational and maintenance costs of vehicles are a significant financial burden, especially since the addition of the fleet is done independently. The combination of these problems makes it difficult for the company to maintain market share and increase profitability. This study aims to identify, analyze and design new business models and strategy landscapes through identification of strengths and weaknesses, as well as external opportunities and threats using the BMC and SWOT framework. The aspects studied include: Value Propositions, Customer Segments, Customer Relationships, Channels, Key Resources, Key Activities, Key Partnerships, Cost Structure, And Revenue Streams. The phenomenon in this study is explored using a case study method. The data collection technique used in this study was through interviews and secondary data collection to obtain a preliminary study related to an in-depth and comprehensive understanding of the business model and utilizing strengths, reducing weaknesses, utilizing opportunities, and countering threats identified through the research process. This study is expected to contribute to knowledge by offering practical insights and recommendations for the latest business models needed by HS Rent Cars to thrive in the car rental business market. By integrating the BMC and SWOT frameworks, this study provides a holistic approach to strategic analysis and formulation as a work plan for HS Rent Cars.